Kelayakan Usahatani dan Pola Saluran Pemasaran Komoditi Bawang Merah di Wilayah Timur dan Barat Kabupaten Sumbawa - Sumarni, Dewi; Nurwahidah, Siti; Yani, Ahmad (Program Studi Agribisnis INSTIPER Yogyakarta, 2024)
This research aims to determine the feasibility of farming and the pattern of shallot marketing channels in the eastern and western regions of Sumbawa Regency. The research area was determined using a purposive sampling technique, starting from the district to the village level which is the center of shallot production. The research was carried out in May-July 2024. The number of samples or farmers in this research was determined by 30 shallot farmers. The analysis method uses descriptive methods, income approach, RC Ratio, and BEP. The research results show that the average income from shallot farming in the western zone is higher, namely: Rp. 77,947,742,- per farm/farmer/season compared to the average income of shallot farming in the eastern zone, which is Rp. 28,058,875,-. per farm/farmer/season. The R/C ratio value of shallot farming in the western zone is greater, namely R/C = 3 compared to the R/C ratio value of the eastern zone, namely R/C = 2. This shows that the efficiency of farming in the western zone is more efficient than with shallot farming in the eastern area of Sumbawa Regency. The BEP price value for the eastern zone is IDR. 10,100 per kilogram, and the BEP price for the west zone is IDR. 8,500,- per kilogram. There are 2 (two) market channel patterns in the western zone of Sumbawa Regency, namely: (1) farmers - retailers at the sub-district market - consumers, (2) farmers - village level collectors - retailers at the sub-district market. Meanwhile, there is only 1 (one) market channel pattern in the eastern zone, namely: farmers - collectors outside the sub-district - wholesalers outside Sumbawa Regency.